Young radio jets breaking free: molecular and HI outflows in their centers. Issue Volume 14:Issue S342(2018) (May 2018) - Morganti, Raffaella; Oosterloo, Tom; Schulz, Robert; Tadhunter, Clive; Raymond Oonk, J. B.
Abstract: Our view of the central regions of AGN has been enriched by the discovery of fast and massive outflows of H I and molecular gas. Here we present a brief summary of results obtained for young (and restarted) radio AGN. We find that H I outflows tend to be particularly common in this group of objects. This supports the idea that the jet, expanding in a clumpy medium, plays a major role in driving these outflows. The clumpiness of the medium is confirmed by VLBI and ALMA observations. The H I observations reveal that, at least part of the gas, is distributed in clouds with sizes up to a few tens of pc and mass ~10 4 M ȯ . A change of the conditions in the outflow, with an increasing fraction of diffuse components, as the radio jets grow, is suggested by the high resolution H I observations. The molecular gas completes the picture, showing that the radio plasma jet can couple well with the ISM, strongly affecting the kinematics, but also the physical conditions of the molecular gas. This is confirmed by numerical simulations reproducing, to first order, the kinematics of the gas.